Extremely Rare Form of Impaction Bilateral Kissing Molars: Report of a Case and Review of the Literature - Tamer Zerener; Gurkan Rasit Bayar; Hasan Ayberk Altug; Serkan Kiran (Case Reports in Dentistry)
Kissing molars (KM) or rosette formation is a term that is used to describe impacted teeth contacting occlusal surfaces in a single follicular space and their roots pointing in opposite directions. In some cases kissing molars can be seen but occurrence of bilateral kissing molars is extremely rare phenomenon in the dental literature and the aetiology of this phenomenon is still unknown. In this paper we describe a case and review of the literature and discuss the management of this pathology. In our case, extremely rare form of impacted bilateral kissing molars was extracted surgically. The decision of extraction of asymptomatic kissing molars represents surgical dilemma. There may be many surgical complications; on the other hand in some cases surgical intervention is unavoidable. Few treatment options were described in the literature. This phenomenon can be sign of various medical conditions that may require further investigation. In this paper, our treatment option is in agreement with the literature suggesting the surgical removal of both teeth at either side of the mandible.